Zavzetost bolnic za zdravljenje osteoporoze - Živčec Kalan, Gordana (Zdravstveno varstvo, 2007)
Background: Studies have shown that the level of patient adherence to osteoporosis treatment is similar to that for other chronic diseases, i.e. approx. 50%. The observed constant decrease in adherence is due to a lack of motivation for long-term treatment. The purpose of our study was to determine the level of patient adherence to once-weekly bisphosphonate, the most commonmedication prescribed for osteoporosis treatment. Methods: A retrospective cohort study was conducted among female patients with primary osteoporosis, who were included in the study by 14 randomly selected Slovene family physicians on the basis of diagnosis classification in a computer-based patient list. For the adherence analysis, the patients were followed for 13 months after the initiation of treatment with once-weekly bisphosphonate. Results: Among the 334 questionnaires returned, 124 met the criteria for the analyisis of patient adherence to once-weekly bisphosphonate therapy. Over the studied 13-month period, the percentage of patients adheringto therapy dropped to 62.9 %. The observed patient compliance was not related to age, level of education, marital status or household size. Thegreatest decrease in adherence was noticed in the first month after treatment initiation due to perceived side effects. Later on, the most common reason for abandoning treatment was failure to ask for a new prescription. Theadherence level of approx. 80 %, reported by the participating doctors, was overestimated. Conclusions: Adherence of patients to osteoporosis therapy tends to be overestimated. The adherence level decreases over time and the proportion of patients abandoning treatment increases, mostly because of side effects and failure of patients to have their prescription refilled. Patients should therefore be monitored for medication adherence and motivated for treatment.
Keywords: bolniki; kronične bolezni; osteoporoza; therapy; zdravljenje